Sasak People’s Resistance Against Mataram-Karangasem and Dutch Colonial Rulers: The Role of Tuan Guru Umar Kelayu - Ahmad Tohri; H. Habibuddin; Abdul Rasyad (Journal of Asian Social Science Research, 2020)
This article discusses the Sasak people’s resistance against MataramKarangasem and Dutch colonial rulers in the 19th century in Lombok, Indonesia. It particularly focuses on Tuan Guru Umar Kelayu and his central role in the emergence of Sasak people’s resistance which transformed into Sasak physical revolution local and global imperialismcolonialism. Using the historical method, this article collected data through observation, in-depth interviews, and documentation. The data analysis involved the historical methods of heuristics, verification or criticism, interpretation, and historiography. The findings show that Sasak people’s resistance was not only caused by economic factors but also related to other factors such as social, cultural, and religious ones. Tuan Guru Umar Kelayu played a key role in the Sasak people’s resistance in that it was under his leadership and influence that the resistance transformed into a physical struggle against MataramKarangasem and Dutch colonialism as seen in Sakra War and Praya War which were led by his students and friends.